2023
DOI: 10.3390/diagnostics13193068
|View full text |Cite
|
Sign up to set email alerts
|

Hashimoto’s Thyroiditis and Papillary Thyroid Carcinoma: A Follow-Up Study in Patients with Absence of Aggressive Risk Factors at the Surgery of the Primary Tumor

Andrea Marongiu,
Susanna Nuvoli,
Andrea De Vito
et al.

Abstract: Hashimoto’s thyroiditis (HT) is often associated with papillary thyroid carcinoma (PC); it is still a matter of controversy whether the behavior of carcinoma is more aggressive or not. During the follow-up, we retrospectively enrolled 97 patients with PC/HT after thyroidectomy without risk factors at the surgery of the primary tumor, such as multifocality/multicentricity, extrathyroid tumor extension, vascular invasion, neck and distant metastases, and aggressive histological variants. HT diagnosis was confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
1
1
0
Order By: Relevance
“…The identification of metastases during follow-up is typically achieved through the use of traditional and highly sophisticated diagnostic imaging procedures, and in all patients, 131 I SPECT/CT has been included with high performance, confirming the reliable results of this procedure reported in the literature [42][43][44][45] also in patients with PC associated to thyroid autoimmune diseases [46,47].…”
Section: Discussionsupporting
confidence: 62%
“…The identification of metastases during follow-up is typically achieved through the use of traditional and highly sophisticated diagnostic imaging procedures, and in all patients, 131 I SPECT/CT has been included with high performance, confirming the reliable results of this procedure reported in the literature [42][43][44][45] also in patients with PC associated to thyroid autoimmune diseases [46,47].…”
Section: Discussionsupporting
confidence: 62%
“…In recent years, researchers have extensively explored the relationship between HT and PTC, particularly the potential impact of HT on LNM in PTC, yet the findings have been inconsistent. Some studies have found a significant effect of HT on the risk of LNM in PTC ( 21 - 23 ). Our findings are in line with this, indicating an increased risk of ipsilateral cervical CLNM among PTC patients with concurrent HT, although the specific mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%